1989
DOI: 10.1037/0022-3514.56.1.117
|View full text |Cite
|
Sign up to set email alerts
|

Private and public self-consciousness and articulation of the self-schema.

Abstract: Two studies assessed recognition memory of interpersonal traits that subjects had rated according to either private self-reference (Study 1) or public self-reference (Study 2). Both studies also administered the Self-Consciousness Scale, which permitted a dual classification of subjects according to private self-consciousness (high and low) and public self-consciousness (high and low). Study 1 revealed a private false alarms effect (FAE), the strength of which was moderated by private selfconsciousness, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
2

Year Published

1989
1989
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 22 publications
0
52
0
2
Order By: Relevance
“…Test-retest reliability at 2 weeks ranged from .73 to .84 (Fenigstein et al, 1975). More recent research has confirmed that the SCS is reliable (e.g., Mittal & Balasubramanian, 1987) and valid (e.g., Nasby, 1989;Schlenker & Weigold, 1990).…”
Section: Methodsmentioning
confidence: 95%
“…Test-retest reliability at 2 weeks ranged from .73 to .84 (Fenigstein et al, 1975). More recent research has confirmed that the SCS is reliable (e.g., Mittal & Balasubramanian, 1987) and valid (e.g., Nasby, 1989;Schlenker & Weigold, 1990).…”
Section: Methodsmentioning
confidence: 95%
“…Kihlstrom & Cantor, 1984;Linville & Carlston, 1994;Nasby, 1989). Specifically, we question the assumption that personal self-schemas always functionally control how we process self-relevant information and thus govern self-conception in the schema-relevant domain.…”
Section: The Present Researchmentioning
confidence: 99%
“…For example, individuals high in private self-consciousness (a) write more detailed self-descriptions (Turner, 1978b), (b) decide more quickly whether trait adjectives describe the self (Mueller, 1982;Turner, 1978c), (c) recall more self-referent material under conditions of incidental learning (Agatstein & Buchanan, 1984;Hull & Levy, 1979, Experiment 1;Turner, 1980), and (d) commit more false alarms to self-descriptive traits but fewer to non-self-descriptive traits during a recognition memory task (Nasby, 1985(Nasby, , 1989) than do individuals low in private self-consciousness.…”
Section: William Nasbymentioning
confidence: 99%